The Legal Power of Public Officers' Decisions Successful in Public Courts - Aji Sudarmaji; Masrur Ridwan; Aryani Witasari (Jurnal Daulat Hukum, 2022)
The aims of this research is to know one of the causes of the emergence of civil cases is the decision of public officials that support and benefit one party, and harm the other party. They feel even more disadvantaged, and feel they have been treated unfairly, because the culprit is considered the source of the problem, namely the decision of the public official who can no longer be challenged in the PTUN (State Administrative Court). The approach used in this research is a normative juridical research method. The object analysis used a qualitative approach, with reference to the existing legal norms in the legislation. The primary data that became the initial basis were civil cases in the Pemalang District Court and the Serang District Court. A birth certificate which is issued if it is not in accordance with and contradicts the applicable legal provisions, it is still possible to be canceled or declared invalid and has no binding legal force by a court decision. However, a birth certificate can be valid and cannot be canceled if it meets certain conditions, both formal and material requirements. In order to cancel a birth certificate, if it is suspected that the issuance is not in accordance with the applicable legal provisions, then the injured party can file a cancellation lawsuit and declare it invalid and does not have binding legal force to the State Administrative Court, but if the submission is in conflict with the provisions of Article 55 of the Law on State Administrative Courts, there is still an opportunity to submit it to the General Court, namely the local District Court to declare that the birth certificate is invalid and has no binding legal force.